Optimum Design of Thrust Oil Bearing for Hard Disk Drive - Mohd Danial, Bin Ibrahim; Hashimoto, Hiromu (2010)
This paper presents the application of optimization method developed by Hashimoto to design oil lubricated thrust bearing for 2.5 inch form factor hard disk drive (HDD). The designing involves optimization of groove geometry and dimensions. Calculation is carried out to maximize the dynamic stiffness of the thrust bearing spindle motor. Static and dynamic characteristics of the modeled thrust bearing are calculated using the divergence formulation method. Results show that by using the proposed optimization method, dynamic stiffnesses values can be well improved with the bearing geometries not being fixed to conventional grooves.